Barn owl nestlings vocally escalate when interrupted by a sibling: evidence from an interactive playback experiment. (November 2018) - Ducouret, Pauline; Dreiss, Amélie N.; Gémard, Charlène; Falourd, Xavier; Roulin, Alexandre
Abstract : To resolve conflicts of interest, animals can vocally signal their resource-holding potential and motivation to compete. This allows conspecifics to adjust their behaviour to each other without fighting physically. Making sure that competitors correctly assess each other's vocal information requires mechanisms to prevent signal interference. Alternating calls with those of an opponent (i.e. waiting until the opponent's call has ended before starting to vocalize) is widely observed in animals and could be partly acquired through learning. Regardless of whether competitors interrupt conspecifics as a signal of dominance or by accident, the information transferred by the interrupted individual is likely to be partly blurred. Interrupted individuals would hence benefit from counterattacking by calling more intensely, indicating to their competitors that calling simultaneously is counterproductive. We tested this 'social feedback' hypothesis in the barn owl, Tyto alba, in which young siblings negotiate vocally over which individual will have priority access to the next food item delivered. It has already been shown that nestlings actively avoid interrupting each other, but it remains untested whether nestlings give social feedback when interrupted. To test this, we developed an 'automated interactive playback' which broadcast calls that either interrupted or did not interrupt the calls of a singleton nestling. When a playback call interrupted a nestling, this individual immediately intensified vocal communication by quickly producing a long call and by producing more calls. As previously shown, this reaction tends to silence competitors and thereby increases the individual's likelihood of obtaining the next food item. Such social feedback could reinforce the evolutionary stability of vocal sibling negotiation as a nonaggressive way to share food. Highlights: Interrupting conspecific calls leads to a partial loss of information. When interrupted, nestlings produce more and longer calls. When interrupted, nestlings respond quicker after the playback call. This social feedback could reinforce the evolutionary stability of communication.